MYOD1 involvement in myopathy - Lopes, Fátima Daniela Teixeira (2018)
[Excerpt] Introduction Myogenic Differentiation 1 (MYOD1) encodes a transcription factor that plays an important role in myogenic determination into mature skeletal muscle [1]. The first loss-of-function mutation of MYOD1 in humans was described in three siblings with perinatal lethal fetal akinesia [2].[...]